Serat Dahor Palak, Sastra Islam Abad XVII - Wijanarko, Fajar (IAIN Surakarta, 2017)
Islam and the dimensions of public believe in Java have their own way to sneak around and survive. Both have an equal position till the society find the now concept, which is Islam Jawa. It is a belief that accommodates between Islam and the traditional beliefs system. The fact of them is also happening on writing era of a manuscript. The last, Syncretism and Sufism are became commonplace in the understanding and development of Islamic literature, which one is Serat Dahor Palak (SDP). The truth of syncretism would be written based on philology approach and method of library research. Inside include of local wisdom from the manuscript which talks about the prophet is way in Hinduism era.